2017
DOI: 10.1073/pnas.1620542114
|View full text |Cite
|
Sign up to set email alerts
|

Facial appearance affects science communication

Abstract: First impressions based on facial appearance predict many important social outcomes. We investigated whether such impressions also influence the communication of scientific findings to lay audiences, a process that shapes public beliefs, opinion, and policy. First, we investigated the traits that engender interest in a scientist's work, and those that create the impression of a "good scientist" who does high-quality research. Apparent competence and morality were positively related to both interest and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 52 publications
5
60
1
Order By: Relevance
“…Unattractive hosts might elicit avoidance motivations, which then spill over to consumer's apartment choices. In fact, similar effects of facial attractiveness on seemingly unrelated preferences have been observed for interest in scientific work (Gheorghiu, Callan, & Skylark, 2017). This account is also supported by our current finding that the effect of attractiveness on apartment prices is driven by unattractive hosts charging lower prices, rather than by attractive hosts charging higher prices.…”
Section: Discussionsupporting
confidence: 86%
“…Unattractive hosts might elicit avoidance motivations, which then spill over to consumer's apartment choices. In fact, similar effects of facial attractiveness on seemingly unrelated preferences have been observed for interest in scientific work (Gheorghiu, Callan, & Skylark, 2017). This account is also supported by our current finding that the effect of attractiveness on apartment prices is driven by unattractive hosts charging lower prices, rather than by attractive hosts charging higher prices.…”
Section: Discussionsupporting
confidence: 86%
“…In HEBP models anomalous diffusion emerges as a consequence of heterogeneity in the particle ensemble, while classical thermodynamics still hold. Heterogeneity is then responsible for long-range correlations, in agreement with approaches based on polydispersity [102]. In particular, in the present approach anomalous behavior is displayed during an intermediate asymptotic transient regime in the Barenblatt's sense [103], thus requiring an underdamped (white noise) Langevin approach.…”
Section: Preliminary Considerationssupporting
confidence: 82%
“…Starting from the Langevin equations associated to each Brownian particle of the ensemble, the HEBP approach leads to anomalous diffusion with uncorrelated white noise. Thus, HEBP models are substantially different from approaches based on the generalized Langevin equation or on Langevin equations with colored noises and, in general, on noises with long-range spatiotemporal correlations with even "anomalous" thermodynamics [102]. In HEBP models anomalous diffusion emerges as a consequence of heterogeneity in the particle ensemble, while classical thermodynamics still hold.…”
Section: Preliminary Considerationsmentioning
confidence: 98%
“…(adherence to social norms and rules) (Brambilla & Leach, 2014;Brambilla, Rusconi, Sacchi, & Cherubini, 2011;Gheorghiu, Callan, & Skylark, 2017;Goodwin, 2015). Second, studies of superficial impressions establish the extent to which social outcomes are based on accessible but often invalid visual cues rather than careful consideration of relevant evidence (Todorov et al, 2015;Todorov & Porter, 2014); this may lead to the development of interventions that minimize bias in important decisions (see Todorov et al, 2015 for examples).…”
Section: A Thin Slice Of Science Communication: Are People's Evaluatimentioning
confidence: 99%
“…One exploration of this issue was provided in a recent paper by Gheorghiu, Callan, and Skylark (2017). Using photos of real scientists, these authors found that interest in a scientist's work was positively predicted by their apparent morality, competence, and attractiveness; in contrast, the extent to which they looked like a "good scientist" (who does important, high-quality work) was positively related to apparent competence and morality, but negatively predicted by apparent sociability and attractiveness.…”
Section: A Thin Slice Of Science Communication: Are People's Evaluatimentioning
confidence: 99%